2013
DOI: 10.1371/journal.pone.0054915
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Abnormal Prion Protein in Genetic Human Prion Diseases Now Possible Using Real-Time QUIC Assay

Abstract: IntroductionThe definitive diagnosis of genetic prion diseases (gPrD) requires pathological confirmation. To date, diagnosis has relied upon the finding of the biomarkers 14-3-3 protein and total tau (t-tau) protein in the cerebrospinal fluid (CSF), but many researchers have reported that these markers are not sufficiently elevated in gPrD, especially in Gerstmann-Sträussler-Scheinker syndrome (GSS). We recently developed a new in vitro amplification technology, designated “real-time quaking-induced conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 7 publications
4
111
0
9
Order By: Relevance
“…The ASA and RT-QuIC are generally analogous to sPMCA, but employ recombinant PrP C instead of brain homogenate as substrate for disease-specific, in vitro, amyloid formation (Atarashi et al, 2007(Atarashi et al, , 2011aColby et al, 2007). RT-QuIC offers the advantage of real-time assessment of amyloid fibril generation and has been successfully applied to many seed sources, some of which are available for antemortem sampling (Atarashi et al, 2011a, b;Elder et al, 2013;Haley et al, 2013;Henderson et al, 2013;McGuire et al, 2012;Orrú et al, 2011Orrú et al, , 2014Peden et al, 2011;Sano et al, 2013;Wilham et al, 2010).…”
Section: Detection Of Prpmentioning
confidence: 99%
“…The ASA and RT-QuIC are generally analogous to sPMCA, but employ recombinant PrP C instead of brain homogenate as substrate for disease-specific, in vitro, amyloid formation (Atarashi et al, 2007(Atarashi et al, , 2011aColby et al, 2007). RT-QuIC offers the advantage of real-time assessment of amyloid fibril generation and has been successfully applied to many seed sources, some of which are available for antemortem sampling (Atarashi et al, 2011a, b;Elder et al, 2013;Haley et al, 2013;Henderson et al, 2013;McGuire et al, 2012;Orrú et al, 2011Orrú et al, , 2014Peden et al, 2011;Sano et al, 2013;Wilham et al, 2010).…”
Section: Detection Of Prpmentioning
confidence: 99%
“…f See reference 19. This is the first report of the detection of PrP C -CCA in the blood of animals within minutes of exposure to TSE inoculum. The use of PrP C -CCA to detect prions in tissues and bodily fluids of TSE-infected hosts has been shown to be as sensitive as a bioassay and has provided insight into a variety of prion diseases (15)(16)(17)(18). The immediate detection of the point-source inoculum was seen following exposure to mucosal surfaces in the nose and gut; the same immediate detection of PrP C -CCA was seen following i.v.…”
mentioning
confidence: 99%
“…However, ongoing validation studies have demonstrated that the outcomes of RT-QuIC reactions depend on the exact conditions employed (biochemical, chemical and physical), as well as the nature of the sample and recombinant substrate. The protocol under evaluation by the National Microbiology Laboratory has been tested extensively for the detection of sporadic CJD (10,11,15,16 ). Using this protocol the Prion Laboratory Section achieved 100% sensitivity and 100% specificity in the evaluation of an external sporadic CJD infected CSF proficiency panel.…”
Section: Summary Of Test Resultsmentioning
confidence: 99%